Combination of Run-1 exotic searches in diboson final states at the LHC - Dias, F.; Gadatsch, S.; Gouzevich, M.; Leonidopoulos, C.; Novaes, S. F. [UNESP]; Oliveira, A.; Pierini, M.; Tomei, T. [UNESP] (Springer, 2016)
We perform a statistical combination of the ATLAS and CMS results for the search of a heavy resonance decaying to a pair of vector bosons with the root s - 8 TeV datasets collected at the LHC. We take into account six searches in hadronic and semileptonic final states carried out by the two collaborations. We consider only public information provided by ATLAS and CMS in the HEPDATA database and in papers published in refereed journals. We interpret the combined results within the context of a few benchmark new physics models, such as models predicting the existence of a W' or a bulk RandallSundrum spin -2 resonance, for which we present exclusion limits, significances, p -values and best -fit cross sections. A heavy diboson resonance with a production cross section of 4-5 fb and mass between 1.9 and 2.0 TeV is the exotic scenario most consistent with the experimental results. Models in which a heavy resonance decays preferentially to a WW final state are disfavoured.
Keywords: Phenomenology of Field Theories in Higher Dimensions